Methods of Prevention and Mitigation of Autoimmune Diseases - A Review of The Literature - Magdalena Celichowska; Zuzanna Bentkowska; Aleksandra Bogoń; Justyna Szpyra; Gabriela Dziuba; Barbara Serkis; Julia Dębińska; Izabela Kałuża; Jagna Golemo; Małgorzata Miazga (Nicolaus Copernicus University in Toruń, 2024)
Introduction and purpose: Autoimmune diseases are conditions where the body's immune system is unable to distinguish between auto- and foreign antigens and mistakenly attacks its cells, tissues, and organs. In recent years it became major public health concern because of the increasing diagnosis rate. Currently, about 5% of the population in Western countries is affected by such diseases, more often in women population. The exact cause of autoimmune diseases is unknown, although most probably it results from a combination of genetic predisposition, environmental risk factors and immune dysregulation. Development of autoantigen-specific lymphocytes and autoantibodies might be decisive in starting the process of autoimmunity. Most common medication used in autoimmune diseases treatment are nonsteroidal anti-inflammatory drugs (NSADs), glucocorticoids, disease-modifying antirheumatic drugs (DMARDs). Additionally, there is biological medication available for many of them. It is known that non-pharmacological interventions, such as specific diets, supplementation or physical exercise is useful to mitigate the disease or even to prevent the body from its onset. Materials and methods: The data for the article was found using the PubMed and Google Scholar websites. The key words used for the search included: 'diet and autoimmunity', 'autoimmunity and estrogens', 'microbiota and autoimmunity'. Articles not written in English, conference abstracts only and duplicated papers were excluded. Conclusions: There is still no cure for autoimmune diseases, although various prevention and mitigation strategies can help manage these conditions and improve quality of life for affected individuals. However, for the use of some of them, evidence-based recommendations are not available. This review highlights current non-pharmacological therapeutic options.